Biblioteki dawniej i dziś. Hybrydowe, cyfrowe...? Jakie będą i co może wpłynąć na ich kształt w przyszłości. - Rożniakowska, Małgorzata; Margas, Marcin; Kitlińska, Iwona; Bógdoł, Piotr (Library of the Lodz University of Technology, 2006)
Początek XXI wieku zapowiada zasadnicze zmiany w zakresie organizacji i funkcjonowania bibliotek w Polsce. Jednym z przejawów tych zmian jest np. działalność pierwszych bibliotek cyfrowych. W pierwszej części referatu przedstawiono krótki rys historyczny zmian charakteru gromadzonych oraz udostępnianych zbiorów do dnia dzisiejszego. Następnie autorzy referatu proponują wizję biblioteki akademickiej przyszłości z punktu widzenia nowych elektronicznych źródeł informacji, popularyzacji technologii papieru elektronicznego i papieru cyfrowego. Uwzględniono też przewidywany postęp w konstrukcji sieci telekomunikacyjnych. Wspomniano również o niektórych podjętych ostatnio inicjatywach digitalizacji na świecie.

The beginning of XXI century is seemed to be the crucial one because of changes which happen presently in the organization and functionality of Polish libraries. The digital libraries activity is that kind of change. The paper presents brief historical outline of the specific changes in acquisition and lending field from the past till now. The core part of the paper presents the future vision of academic library from the point of view of the new emerging technologies in IT and telecommunications systems. The middle part of the article is focused on the problems concerning the development of new electronic sources of information, the electronic and digital paper which may influence and just have affected the libraries. Possible development of structures of telecommunication networks is also included. The last part of the article describes already have started a few initiatives of digitalization in the world.
Libraries past and today. Hybrid, digital…? What will be and what can affect their models in future